Oligohydramnios and Fetal Outcome: A Review - Khatun, Tarannum; Ansari, Akhtar Alam; Hamid, Irfan; Gupta, Ravi Shankar; Ahmad, Md. Parwez (Med Phoenix, 2017)
Oligohydramnios is a threatening condition to fetal health and is associated with increased fetal morbidity. These conditions are often missed and patient may not seek appropriate treatment at appropriate time that often increases risk of numerous conditions. Early detection of oligohydramnios and its management may help in reduction of perinatal morbidity and mortality one side and decreased caesarean deliveries on the other side. A search in Google scholar, PubMed, Medline, EMBASE was performed using key words. Inclusion criteria for articles selection were singleton pregnancy, definition of olgohydramnios as AFI <5 cm, AF assessment at 37-42 gestational weeks. The searched revealed numerous research articles which is further refined. It is found that oligohydramnios is associated with Intrauterine Growth Restriction (IUGR), small for gestational age (SGA), prolonged labour, caesarian section (C/S) for fetal distress (FD), meconium stained liquor, Low Apgar score and Neonatal Intensive Care Unit (NICU) admission. Women with oligohydramnios are associated with higher fetal risk but can expect a safe delivery and good outcome for which proper fetal surveillance and regular Antenatal care (ANC) visits are required. MED Phoenix Volume (1), Issue (1) July 2016, page: 23-30